2015
DOI: 10.1371/journal.pgen.1005105
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Control of Light Induced Chromatin Remodeling and Gene Activation in Neurospora

Abstract: Light is an important environmental cue that affects physiology and development of Neurospora crassa. The light-sensing transcription factor (TF) WCC, which consists of the GATA-family TFs WC1 and WC2, is required for light-dependent transcription. SUB1, another GATA-family TF, is not a photoreceptor but has also been implicated in light-inducible gene expression. To assess regulation and organization of the network of light-inducible genes, we analyzed the roles of WCC and SUB1 in light-induced transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 62 publications
(75 reference statements)
5
67
0
Order By: Relevance
“…Combining genes from all time points revealed that ADV-1 potentially controls the expression of 1029 unique gene targets (Table S3), representing ∼10% of the predicted 9730 N. crassa genes. Several of the predicted ADV-1 target genes are also predicted targets of the WCC, and/or of two downstream TFs that are direct targets of the WCC, CSP-1, and SUB-1, suggesting combinatorial control for these genes (Smith et al 2010; Sancar et al 2011, 2015a) (Table S3). The distribution of ADV-1 binding peaks for each time point, based on their positions relative to the transcriptional start site from the annotated genes in the N. crassa genome (http://www.broad.mit.edu/annotation/genome/neurospora/), were examined (Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining genes from all time points revealed that ADV-1 potentially controls the expression of 1029 unique gene targets (Table S3), representing ∼10% of the predicted 9730 N. crassa genes. Several of the predicted ADV-1 target genes are also predicted targets of the WCC, and/or of two downstream TFs that are direct targets of the WCC, CSP-1, and SUB-1, suggesting combinatorial control for these genes (Smith et al 2010; Sancar et al 2011, 2015a) (Table S3). The distribution of ADV-1 binding peaks for each time point, based on their positions relative to the transcriptional start site from the annotated genes in the N. crassa genome (http://www.broad.mit.edu/annotation/genome/neurospora/), were examined (Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the poor overlap between the differentially expressed genes and the direct targets of ADV-1 revealed that binding does not necessarily equate with a change in mRNA levels. This may be due to binding and compensation by other TFs, such as WCC, SUB-1, and CSP-1 (Sancar et al 2011, 2015a; Smith et al 2010) (Table S3), and/or may reflect that regulatory mechanisms other than light are also important for controlling the expression of these ADV-1 targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a certain subset of genes in a sub - 1 mutant have altered amplitude of induction which suggests that factors other than SUB-1 are required for activating these genes, and that SUB-1 takes up an ancillary role as a modulator of gene expression (Chen et al , 2010a). This ancillary role was brought to the fore when it was found that for a subset of light-induced genes, although WCC was primarily essential for induction, SUB-1 facilitates chromatin remodeling by interacting with a transcription factor FF-7 (containing a putative O-acetyl transferase domain) in combination with WCC, thereby modulating the extent of induction of their common target genes (Sancar et al , 2015). Interestingly, SUB-1 and FF-7 regulate the expression a much greater fraction of non-light induced genes, suggesting that this might be a general transcription regulatory module that is co-opted during the light response.…”
Section: N Crassa: a Model Organism For Studying Photobiologymentioning
confidence: 99%
“…Recently, it was demonstrated that light activation of WC-1 and -2 is related to nucleosome removal at their target promoters. Furthermore, sub-1 (a WC-1-and -2-dependent gene that codes for a GATA-type transcription factor) is necessary for efficient remodeling of certain nucleosomes (31).…”
mentioning
confidence: 99%